2016
DOI: 10.1097/scs.0000000000003095
|View full text |Cite
|
Sign up to set email alerts
|

Florid Cemento-Osseous Dysplasia Simultaneous the Chronic Suppurative Osteomyelitis in Mandible

Abstract: The aim of the present paper was to relate a clinical patient of florid cemento-osseous dysplasia simultaneous the chronic suppurative osteomyelitis, highlighting their clinical, radiographic, and histological characteristics, as well as their diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…However, if an invasive procedure, such as a tooth extraction, is absolutely necessary, it must be done with caution not to cause infection of the bone. 9 10 This report describes a case of postoperative infected FCOD that became symptomatic and needed additional treatment.…”
mentioning
confidence: 99%
“…However, if an invasive procedure, such as a tooth extraction, is absolutely necessary, it must be done with caution not to cause infection of the bone. 9 10 This report describes a case of postoperative infected FCOD that became symptomatic and needed additional treatment.…”
mentioning
confidence: 99%
“…There are some cases of FCOD in which the patients report mild and intermittent pain in the affected area, especially after trauma or secondary infection [3,8,9,16]. In this case report, the patient has been followed up for a long period (thirteen years) and she has reported no symptoms associated with the lesion.…”
Section: Discussionmentioning
confidence: 93%
“…A challenge in the orthodontic management of patients with COD occurs when tooth extraction is indicated. This procedure can result in the exposure of poorly vascularized sclerotic cemental masses in the oral cavity, which can lead to infection and consequent secondary osteomyelitis [1,2,8]. Pulp vitality tests should be carried out along with reinforcement of oral hygiene [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in the past literature reported that hormone imbalance affects the occurrence of FCOD(14). Some cases have been reported to show a family history, but most cases appear to represent isolated instances(10,11,12). However, since gender, race, and age are important factors for the diagnosis of NPDC, they must be considered to add FCOD for differentiation when lesions are observed in middle-aged Asian women, as in this case.…”
mentioning
confidence: 91%